Development of Ethno-PMRI based E-Worksheet with Mayang Rontek Dance Context on Plane Figures of Geometry Materials - Putri, Taszkia Aulia; Fadilah, Nurul; Anjasari, Tika; Sari, Yurizka Melia (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
The e-worksheet is an interactive tool that allows students to access questions and explore information electronically, supporting their understanding of the concepts being studied. This study aims to develop a valid and effective e-worksheet based on the Ethno-Pendidikan Matematika Realistik Indonesia (PMRI) approach, incorporating the context of the Mayang Rontek Dance, to assist students in learning geometry. The research followed the ASSURE model, which includes six stages: analyzing students' needs, defining objectives, selecting appropriate media and materials, engaging learners, and evaluating and revising the developed e-worksheet. The e-worksheet underwent validation by three experts using Aiken’s analysis technique. Limited trials were conducted with six junior high school students, followed by field trials with twenty-nine students. The results revealed that the e-worksheet was valid, with Aiken indices ranging from 0.59 to 0.89. Statistical analysis using the Wilcoxon test on pre-test and post-test scores successfully rejected the null hypothesis, indicating that the e-worksheet effectively improved students' test scores. Furthermore, the practicality test yielded a score of 84.97%, demonstrating the e-worksheet's high level of practicality. Thus, the developed e-worksheet has been validated as both effective and practical in enhancing students’ understanding of geometry. The integration of the Ethno-PMRI approach and GeoGebra is expected to further enrich students' comprehension of mathematical concepts and their connection to local culture.